2012
DOI: 10.1587/transcom.e95.b.27
|View full text |Cite
|
Sign up to set email alerts
|

A Multiband Monopole Antenna with Modified Fractal Loop Parasitic for DCS 1800, WLAN, WiMAX and IMT Advanced Systems

Abstract: A multiband monopole antenna with modified fractal loop parasitic is presented. By adding bow-tie patches and a modified fractal loop to the sides and bottom of a strip line monopole, respectively, the presented antenna can generate the multi-resonant frequencies for the application of wireless communication systems. The characteristics of the presented antenna have been examined by using the simulation software. The comparison between the simulation and measured results confirm the good agreement. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Also, the third resonant frequency of the antenna was occurred due to the slot of the U-shape stub. Especially, the multiband antenna composing of the monopole strip line connecting to the bow-tie patch to radiate at the first and third resonant frequencies, respectively, and the parasitic loop placed on the bottom layer responding to the second resonant frequency was presented in [11]. As the previous reviews, the multiband antennas designed by using multiple resonator technique can radiate independently electromagnetic field at each resonant frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the third resonant frequency of the antenna was occurred due to the slot of the U-shape stub. Especially, the multiband antenna composing of the monopole strip line connecting to the bow-tie patch to radiate at the first and third resonant frequencies, respectively, and the parasitic loop placed on the bottom layer responding to the second resonant frequency was presented in [11]. As the previous reviews, the multiband antennas designed by using multiple resonator technique can radiate independently electromagnetic field at each resonant frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Among the well‐known multiband antenna prototypes, the planar and coplanar monopole antennas of various configurations have become popular in the implementation of wireless systems because they provide a cost effective and low profile antenna designs with omnidirectional radiation patterns. Multiband operation of antennas can be achieved by using multiresonators so that each resonator radiates independently at each operating frequency . However, it has been found that using these multiband design techniques, the antenna characteristics could not be easily adjusted due to the effects of mutual couplings between resonators.…”
Section: Introductionmentioning
confidence: 99%
“…Various kinds of multi-band antennas have been reported for WLAN, DCS 1,800, and IMT-2000 applications [1][11]. In particular, several papers related to the study of rectangular, ring-shaped monopole antennas have proposed these types of devices [12]~ [15].…”
Section: ⅰ Introductionmentioning
confidence: 99%